Réponses

2013-11-25T09:43:27+01:00
A= (2x+5) (4x-9)+(3x+8)(2x+5)
=
(2x+5)(4x-9+3x+8)
=(2x+5)(7x-1)
                                                                                      
B=(6x+1)²-(3x+5)(6x+1)   
=(6x+1)(6x+1)-(3x+5)(6x+1)   
=(6x+1)(6x+1-3x-5)
=(6x+1)(3x-4)

C=25x²-20x+4
=(5x-2)²               

D=49x²-36  
=(7x+6)(7x-6)     
2013-11-25T09:43:28+01:00
A = (2x+5)(4x-9)+(3x+8)(2x+5)
A = (2x+5)[(4x-9)+(3x+8)]
A = (2x+5)(4x-9+3x+8)
A = (2x+5)(7x-1)

B = (6x+1)²-(3x+5)(6x+1)
B = 
(6x+1)[(6x+1)-(3x+5)]
B = (6x+1)(6x+1-3x-5)
B = (6x+1)(3x-4)

C = 25x²-20x+4
C = (5x-2)²

D = 49x²-36      
D = (7x-6)(7x+6)